Evidence on the Demographic Transition - Lehr, Carol Scotese (The Review of Economics and Statistics, 2009)
This paper finds that fertility responds to productivity differently depending on the economy's stage of development. At low levels of development, productivity increases will increase fertility, while at the more advanced stages of development, productivity increases lower fertility. During the process, there may be important interaction effects between productivity and education demand. Increases in secondary education demand generate fertility declines regardless of the stage of development.